Effect of Service Quality on Customer Satisfaction at PT Pegadaian Watansoppeng Branch - Dewi Sartika; Ruliaty Ruliaty; Aulia Aulia (CV. AFDIFAL MAJU BERKAH, 2024)
This study aims to analyze the effect of quality on customer satisfaction at PT Pegadaian watansoppeng branch. The research method used is quantitative with a descriptive approach. The research location was carried out at PT.Pegadaian Watansoppeng Branch, soppeng Regency, for 3 months. Data were collected through questionnaires and analyzed using descriptive statistical methods through the Statistical Package for the Social Science (SPSS) 27 application. Based on the results of this study, the t-test results that have been obtained on the variable service quality (X) on customer satisfaction (Y) obtained by ujit, service quality shows a sig value smaller than the significance level (0.000<0.05), or the t-count value is greater than the t-table (5.390> 1.670) so that the hypothesis is accepted. This shows that Service Quality has a positive and significant effect on Customer Satisfaction